Effect of Banditry on School Attendance Among Students in Sakaba Local Government Area, Kebbi State, Nigeria - Mairo Danjumma; Abubakar Aliyu; H. S. Aliero (International Journal of Educational and Psychological Sciences, 2024)
This research work studied the Effect of Banditry on School Attendance among Students in Sakaba Local Government Area of Kebbi State, Nigeria. This study used a mixed method. This is a case study and the population of the study comprised 5434 students, 60 teachers and 2717 parents. The sampling techniques used were purposive sampling for the selection of schools, systematic sampling for the selection of parents and convenient sampling for the selection of teachers. Two instruments for data collection were used; Focus Group Discussions (FGD) and a Questionnaire. The validity of the instruments was determined by experts in the field of measurement and evaluation while a reliability index of 0.76 for the Questionnaire was arrived at after conducting a test re test. The reliability of the Qualitative instrument was determined through administration on a wide range of participants outside the study area. Analysis was done using Statistical Package for Social Sciences (SPSS) version 20 and percentages. The findings were presented in the form of tables, figures and analytical descriptions using themes and sub-themes. The study revealed the problems faced and the effects of Banditry on Secondary School attendance such as: the feeling of fear and anxiety, trauma and psychological impact, disruption of daily school routines and extra-curricular activities, lack of safety measures, displacement and destruction of infrastructure and economic impact among others. The study recommended that to ensure safety, security and safe learning environment, parents and guardians should be engaged in discussion on safety measures.